Displacement piles - classification and new methods for the calculation of bearing capacity - Gwizdała, Kazimierz; Więcławski, Paweł (Scientific Review Engineering and Environmental Sciences (SREES), 2020)
The paper presents technological changes concerning not only the method of construction, but also the materials used. Another aspect is the methods of calculating the load-bearing capacity and settlement of piles. With acceptance for use the PN-EN:1997-1:2008 standard in 2010, it was necessary to change the approaches applied that based on many years of experience and tradition. The best method in this case is to forecast the full load-settlement characteristics. On the basis of the collected data, a comparative analysis of particular displacement piles technologies was made. The usefulness of individual methods of load-bearing capacity calculation depending on the pile technology was determined.